Ductilisation and fatigue life enhancement of selective laser melted AlSi10Mg by friction stir processing. (September 2019) - Santos Macías, Juan Guillermo; Elangeswaran, Chola; Zhao, Lv; Van Hooreweder, Brecht; Adrien, Jérôme; Maire, Eric; Buffière, Jean-Yves; Ludwig, Wolfgang; Jacques, Pascal J.; Simar, Aude
Abstract: In the effort of expanding the already existing applications of additively manufactured parts, improving mechanical performance is essential. Friction stir processing (FSP) is a promising post-treatment solution to tackle this issue. FSP of selective laser melted AlSi10Mg leads to the globularisation of the Si-rich eutectic network, microstructural homogenisation and porosity reduction. These features have been characterised using in and ex situ mechanical testing and different imaging techniques. A significant modification of the damage mechanism is reported with an increase of the fracture strain from 0.1 to 0.4 after FSP and an enhancement over two orders of magnitude in fatigue life. Graphical abstract: Unlabelled Image